Thermal manipulation modifies embryonic growth, hepatic free amino acid concentrations, and hatching performance in layer-type chicks - Han, Guofeng; Li, Sheng; Li, Yansen; Tran, Phuong V.; Furuse, Mitsuhiro; Bungo, Takashi; Chowdhury, Vishwajit S.; Bai, Zongchun; Li, Chunmei (Frontiers in Veterinary Science, 2022)
Thermal manipulation (TM) of incubation temperature has been demonstrated to alter metabolism and post-hatch thermotolerance in broiler strains (meat-type chickens). Less reports were focused on layer-type chickens and there was no report on amino acid metabolism during TM in layer-type embryos. In this study, we investigated the effects of TM on embryonic development, hepatic amino acid metabolism and hatching performance in layer-type chickens. Fertilized eggs were incubated under control thermoneutral temperature (CT, 37.6°C) and TM with high temperature (TMH, 39°C, 8 h/day) or low temperature (TML, 20°C, 1 h/day) from embryonic day (ED) 8 to ED 15. The embryonic weight and relative embryonic weight (yolk free embryonic weight to the initial egg weight) were significantly declined in TML group at ED 13 (P<0.01) and ED 16 (P<0.0001), and was significantly increased (P<0.001) in TMH group at ED 16, in comparison with the embryos in the CT group. The concentrations of all of hepatic free amino acids were significantly increased (P<0.01) with embryonic development. Interestingly, TMH and TML caused similar effects on hepatic amino acid metabolism, in which most of the essential and non-essential amino acids were significantly declined (P<0.05) under TM treatments at ED 13, but not affected at ED 16. Until hatching, TML, but not TMH, caused significant (P<0.05) delay (31-38 min/day from ED 8) on incubation duration. The hatchability in TML group was lower than other two groups, which indicated that 20°C as cold stimulate was not suitable for layer embryos. The body weight, yolk weight, yolk free body mass and chick quality were not affected by TM treatments. However, the relative weight of liver, but not heart, was significantly reduced (P<0.05) at hatching by TML treatment. In conclusion, TML, but not TMH, caused to delay embryogenesis and affected internal organ of chicks at hatch. Similar changes in amino acid metabolism under TMH and TML indicated that thermal stress induced by both high and low extreme ambient temperatures influences embryonic amino acid metabolism in a similar fashion in layer-type embryos.